Pharmacological and pre-clinical safety profile of rSIV.F/HN, a hybrid lentiviral vector for cystic fibrosis gene therapy - Moiseenko,A; Sinadinos,A; Sergijenko,A; Pineault,K; Saleh,A; Nekola,K; Strang,N; Eleftheraki,A; Boyd,AC; Davies,JC; Gill,DR; Hyde,SC; et al. (European Respiratory Journal, 2025)
Rationale and objectiveCystic fibrosis (CF) is caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. CFTR modulators offer significant improvements, but ∼10% of patients remain nonresponsive or are intolerant. This study provides an analysis of rSIV.F/HN, a lentiviral vector optimised for lung delivery, including CFTR protein expression, functional correction of CFTR defects and genomic integration site analysis in preparation for a first-in-human clinical trial.MethodsAir–liquid interface cultures of primary human bronchial epithelial cells (HBECs) from CF patients (F508del/F508del), as well as a CFTR-deficient immortalised human lung epithelial cell line mimicking class I (CFTR-null) homozygous mutations, were used to assess transduction efficiency. Quantification methods included a novel proximity ligation assay for CFTR protein expression. For assessment of CFTR channel activity, Ussing chamber studies were conducted. The safety profile was assessed using integration site analysis and in vitro insertional mutagenesis studies.ResultsrSIV.F/HN expressed CFTR and restored CFTR-mediated chloride currents to physiological levels in primary F508del/F508del HBECs as well as in a class I cells. In contrast, the latter could not be achieved by small-molecule CFTR modulators, underscoring the potential of gene therapy for this mutation class. Combination of rSIV.F/HN-CFTR with the potentiator ivacaftor showed a greater than additive effect. The genomic integration pattern showed no site predominance (frequency of occurrence ≤10%), and a low risk of insertional mutagenesis was observed in an in vitro immortalisation assay.ConclusionsThe results underscore rSIV.F/HN as a promising gene therapy vector for CF, providing a mutation-agnostic treatment option.